Penguatan identitas nasional generasi muda di era modern dalam menghadapi perkembangan teknologi - hakimah, ahmadah latifatul (Maliki Interdisciplinary Journal, 2026)
Technological development is something that cannot be separated from everyday life, especially for the younger generation, technology not only influences the younger generation in interacting but also plays a role in determining their identity. This journal aims to analyze how the influence of strengthening national identity for the younger generation to face the development of the times. Through a literature review method that focuses on collecting data and information from various trusted sources such as journals and other trusted sources that discuss national identity and the influence of technology on the younger generation. From this study concludes that technological developments bring positive and negative impacts, technology can be used as a means of expression and opinion, but also causes the entry of foreign cultures that can weaken national identity. Therefore, efforts and strategies are needed such as using technology wisely, reducing consumptive habits, as well as the role of families, schools and governments. With these efforts it is hoped that the younger generation can maintain national identity amidst the development of the times and technology.